Application Practice and Innovative Exploration of AIED Technology in the Education of Rural Left-behind Children - Yi, Xiya; Liu, Yue (IC-ITECHS, 2024)
This study focuses on the application practice and innovative exploration of Artificial Intelligence in Education (AIED) in promoting the education of rural left-behind children. By comprehensively utilizing methods such as literature review and field case analysis, and through in-depth mining and visual presentation of core literature in the field of AIED over the past five years, the study aims to reveal its positive roles in balanced allocation of educational resources, improvement of teaching quality, and innovation of learning modes. The research findings indicate that AIED technology effectively alleviates the shortage of educational resources faced by rural left-behind children, and significantly narrows the urban-rural education gap, by integrating high-quality educational resources from across the country and even globally, building personalized learning platforms, and implementing a dual-teacher teaching mode of "online master teacher + offline tutoring". In terms of enhancing learning outcomes, AIED technology not only improves students' academic performance but also strengthens the mental health of left-behind children through intelligent mental health monitoring and intervention.